Recombinant AfusinC, an anionic fungal CSαβ defensin from Aspergillus fumigatus, exhibits antimicrobial activity against gram-positive bacteria - Contreras, Gabriela; Braun, Markus S.; Schäfer, Holger; Wink, Michael (PLOS ONE, 2018)
Antimicrobial peptides (AMPs) are short and generally positively charged peptides found in a wide variety of organisms. CSαβ defensins are a group of AMPs. These defensins are composed of an α-helix and a β-sheet linked by three or four disulphide bridges. In this study, we describe the antimicrobial activity of an anionic CSαβ fungal defensin from Aspergillus fumigatus, AfusinC. AfusinC was recombinantly produced as a fusion protein in Escherichia coli. The tag was removed by proteolytic cleavage, and AfusinC was purified by size exclusion chromatography. About 0.8 mg of recombinant AfusinC was obtained from 1 L of culture. Recombinant AfusinC was active against mainly gram-positive bacteria including human pathogens and a multiresistant-strain of A. aureus. Additionally, AfusinC showed bactericidal effect against Micrococcus luteus.
Gesehen am 03.06.2019